PREDIKSI DAMPAK SUBSTITUSI KERTAS LAINER OLEH KERTAS MEDIUM PADA KANTONG GELOMBANG MENGGUNAKAN PERSAMAAN EMPIRIS (PREDICTION OF SUBSTITUTION IMPACT OF KRAFT LINER BY CORRUGATING MEDIUM IN CORRUGATED BOARD BY USING EMPIRICAL FORMULA) - Taufan Hidayat; Rina Masriani; Dadang Setiawan Asid (Center for Pulp and Paper, 2008)
Corrugated board is made from kraft liner and corrugating medium. The growth of box market indicates that there are the increasing demand of corrugated board with reasonable price. Converters then change the kraft liner by corrugating medium to produce cheaper corrugated board. This substitution will influence the quality of corrugated board due to the lower quality of corrugating medium. This paper tries to predict the properties of corrugated board from the properties of the components, when the replacing happen.The prediction based on the propagation properties from kraft liner and corrugating medium to corrugated board. A certain amounts of kraft liner and corrugating medium coming from Indonesian paper mills were sampled and tested. The results are used to make a simulation of corrugated board compositions. The prediction of corrugated board performance are approached by box compression strength, calculated by McKee formula, and the containability, predicted by bursting strength. The box compression strength and bursting strength between the general corrugated board and subtitued corrugated board are then compared. The lowest of performance decreasing of corrugated board achieved at corrugated board 250 g/m2.Keywords: kraft liner, corrugating medium, corrugated board, box compression stregth, bursting strengthenINTISARIKarton gelombang adalah karton yang dibentuk oleh kertas lainer sebagai penyekat dan pelapis dan kertas medium sebagai komponen gelombangnya. Perkembangan pasar menunjukkan adanya kebutuhan yang tinggi terhadap karton gelombang dengan harga murah. Oleh karena itu para konverter mengganti komponen lainernya dengan kertas medium. Penggantian ini tentu akan berdampak pada kualitas karton gelombang, mengingat mutu kertas medium dibawah mutu kertas lainer. Tulisan ini mencoba memprediksi kinerja kotak karton gelombang jika substitusi dilakukan.Prediksi dilakukan berdasarkan propagasi karakteristik kertas lainer dan medium terhadap karton gelombang. Untuk itu dilakukan pengujian sejumlah kertas lainer dan medium dari berbagai sumber yang mewakili hampir seluruh produk kertas lainer medium yang beredar di Indonesia. Dari hasil uji tersebut kemudian dilakukan simulasi variasi berbagai pasangan kertas lainer dan kertas medium, kemudian dihitung nilai BCT prediksinya dengan persamaan McKee dan membandingkannya dengan nilai BCT KKG jika kertas lainer disubstitusi oleh kertas medium. Hal yang sama dilakukan untuk sifat ketahanan retak karton gelombang. Hasil prediksi menunjukkan bahwa penurunan kinerja terendah terjadi pada karton gelombang 250 g/m2.Kata kunci: Kertas liner, kertas medium, karton gelombang, kotak karton gelombang, box compresion test (BCT), ketahanan retak